#132 : Outcomes and Related Risk Factors of Heterotopic Pregnancy in IVF-ET Cycles - Xianghua Dong; Mingxia Gao (Fertility & Reproduction, 2023)
Background and Aims: In vitro fertilization-embryo transfer (IVF-ET) has demonstrated significant success in treating infertility, but it can also introduce complications and risks such as heterotopic pregnancy (HP), which can lead to ectopic pregnancy rupture and bleeding, potentially endangering the patient’s life and fertility. This study aims to investigate the outcomes and associated risk factors of HP following IVF-ET, providing clinical insights for HP treatment. Methods: A retrospective analysis was conducted on the clinical data, treatment, and pregnancy outcomes of patients with HP after IVF-ET admitted to First Hospital of Lanzhou University from Jan. 2012 to Dec. 2022. Statistically significant risk factors were identified and subjected to logistic regression analysis. Results: Our data revealed a HP incidence of 1.27%. Among the 66 patients with HP, 5 underwent conservative treatment (7.58%, 5/66) with a live birth rate of 25.00% (1/5). Laparoscopic surgery was performed on 61 cases (92.42%, 61/66), with a live birth rate of 77.05% (47/61). Among patients receiving laparoscopic surgery, 49.18% (30/61) had a history of pelvic surgery, 39.34% (24/61) underwent a fresh IVF cycle, and 60.66% (37/61) had a freeze-thaw cycle. The live birth rate was 83.67% (41/49) for those with a visible fetal germ and 85.37% (35/41) for those with a visible fetal heartbeat prior to surgery. Further logistic regression analysis revealed that the average diameter of the intrauterine gestational sac prior to laparoscopic surgery, the absence of a fetal germ and fetal heartbeat within the intrauterine gestational sac, and an extended duration of laparoscopic surgery were risk factors affecting pregnancy outcomes (P<0.05). Conclusion: The incidence of HP in IVF-ET is much higher than in natural conception. Laparoscopic surgery is an effective treatment for HP, which does not seem to impact the ongoing pregnancy and live birth rates of the intrauterine gestational sac. However, the patient’s pregnancy outcome can be influenced by several factors, such as the average diameter and development of the intrauterine gestational sac prior to surgery, as well as the duration of the surgery.